Recognizing children's emotions in child abuse and neglect - Camilo, C. (2021)
Past research has suggested that parents' ability to recognize their children's emotions is associated with an enhanced quality of parent–child interactions and appropriateness of parental caregiving behavior. Although this association has also been examined in abusive and neglectful parents, the results are mixed and do not adequately address child neglect. Based on the Social Information Processing model of child abuse and neglect, we examined the association between mothers' ability to recognize children's emotions and self- and professionals-reported child abuse and neglect. The ability to recognize children's emotions was assessed with an implicit valence classification task and an emotion labeling task. A convenience sample of 166 mothers (78 with at least one child referred to Child Protection Services) completed the tasks. Child abuse and neglect were measured with self-report and professionals-report instruments. The moderating role of mothers' intellectual functioning and socioeconomic status were also examined. Results revealed that abusive mothers performed more poorly on the negative emotions recognition task, while neglectful mothers demonstrated a lower overall ability in recognizing children's emotions. When classifying the valence of emotions, mothers who obtained higher scores on child neglect presented a higher positivity bias particularly when their scores in measures of intellectual functioning were low. There was no moderation effect for socioeconomic status. Moreover, the results for child abuse were mainly observed with self-report measures, while for child neglect, they predominantly emerged with professionals-report. Our findings highlight the important contribution of the social information processing model in the context of child maltreatment, with implications for prevention and intervention addressed.